Efektivitas Metode Filtrasi Pada Pengolahan Limbah Tambak Udang Di Sekolah Vokasi IPB University - Putri Azistia, Alisa; Andira, Djenar; Kusuma Dewi, Fatma; Rezha Rizhkiawan, Rafcha; Yusafri Satria, Ridho; Nurfadilah, Siti; Angreani, Tiara; Wiyatin; Tribuana Tunggadewi, Andini; Alif Dirapraja, Muhammad (BULLET : Jurnal Multidisiplin Ilmu, 2024)
Shrimp farming produces wastewater as a byproduct. Wastewater management is necessary to reduce environmental pollution. The purpose of this study is to determine the effectiveness of filtration media using physical and chemical parameters as indicators.  The method applied is filtration by utilizing filter media in the form of silica sand, zeolite stone, greensand sand, manganese zeolite, bioball, and activated carbon.  Shrimp pond waste is flowed through three stages of filtration consisting of a pre-filter to increase pH, filter 1 to filter particles, and filter 2 to improve chemical parameters. The results showed that wastewater after the filtration process has a characteristic blackish turbid color and is odorless. Chemically, there was a decrease in pH from 8.8 to 5.4, a decrease in DO from 4.135 mg / L to 2.895 mg / L, and a decrease in hardness from 96.5 mg / L to 96 mg / L. The decrease in DO content and hardness occurs due to a reduction in the load of organic matter, while the decrease in pH is influenced by the interaction between contaminants and filtration media. Wastewater treatment with filtration methods has proven to be quite effective using predetermined materials.